Formation Tout au Long de la Vie à une conduite sûre : enjeux et limites d'un dispositif d'apprentissage - Marianne Abramovici; Catherine Maman (Université de Provence, 2013)
In this paper we consider the training to driving and Road Security in the more general context of Long Life Learning (LLL). This work focuses on the importance of gradual and continuous access to the skills necessary for the acquisition of safe driving. During 2O years, progress have been made in terms of Road Security, nevertheless, the topic justifies the need to strengthen the training of trainers but also in order to develop LLL, the facilitation and coordination of the network of actors contributing to this training.